A method for microscopic unsaturated soil-water interaction analysis based on DDA. (April 2019) - Guo, Longxiao; Li, Tonglu; Chen, Guangqi; Yu, Pengcheng; Peng, Xinyan; Yang, Deguang
Abstract: Unsaturated soil is a three-phase discontinues system, and microscopic analysis can provide an intrinsic understanding for macroscopic mechanical behavior of the soil. Discontinuous Deformation Analysis (DDA) has the advantage for analyzing the material like granular aggregates. Based on capillary mechanics, a newly developed algorithm is applied in conventional DDA code, which treats a DDA element as an ideal soil particle and exerts capillary force among elements. Then, to validate the extended method, an ideal microscopic soil model is established, and the simulation results are in good agreement with typical analytical solutions. It indicates that the developed DDA is reliable and applicable to explore unsaturated soil behaviors microscopically.